Investigation of electrical conductivity and radical scavenging activity of boron phosphate filled polypyrrole nanocomposites - Ugraskan, Volkan; Bilgi, Mesut; Yazici, Ozlenn (TAYLOR & FRANCIS INC, 2023)
In this study, the effects of the nanoscaled boron phosphate (BP) addition to polypyrrole (PPy) were investigated. Firstly, the composites containing different weight ratios of BP were prepared and characterized using Fourier-Transform Infrared-attenuated total reflection (FTIR-ATR), UV-vis, X-ray diffraction (XRD), and scanning electron microscopy analyzes. FTIR-ATR analyzes indicated the electrostatic interactions between PPy and BP molecules whereas UV-vis analyzes showed that charge carrier concentration increased with the addition of BP. The electrical conductivity measurements indicated that the electrical conductivity of the pristine PPy increased from 11.1 Scm(-1) to 160.6 Scm(-1) with the addition of 20% BP by weight. Furthermore, with the addition of 20% BP, the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH center dot) scavenging activity of PPy was significantly increased from 30.59 +/- 0.5% to 49.18 +/- 1.17% while 2,2 '-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) radical (ABTS(center dot+)) scavenging activity improved from 21.97 +/- 1.07% to 29.70 +/- 0.04%. The observed data have shown that electrically conductive PPy/BP nanocomposites can be a promising component for antioxidant materials.
Keywords: Electrical properties; radical scavenging activity; composite; polypyrrole; boron phosphate; NEUTRON-CAPTURE THERAPY; ANTIOXIDANT ACTIVITY; POLYMERS; BIOCOMPATIBILITY; NANOPARTICLES; POLYANILINE; NANOTUBES; MEMBRANE; PROPERTY; Polymer Science